Ab initio prediction of structuring/mesoscale inhomogeneities in surfactant-free microemulsions and hydrogen-bonding-free microemulsions. Issue 15 (1st April 2019) - Hahn, Maximilian; Krickl, Sebastian; Buchecker, Thomas; Jošt, Gašper; Touraud, Didier; Bauduin, Pierre; Pfitzner, Arno; Klamt, Andreas; Kunz, Werner
Abstract : Prediction of microemulsion-like structuring in surfactant-free and hydrogen-bonding-free systems. Abstract : In this paper, we consider the influence of H-bond donor and acceptor functionalities on the formation of mesoscale inhomogeneities in ternary systems. It was found that hydrogen-bonding re-enforces such structures, but is not necessarily a prerequisite for the occurrence of mesoscale, microemulsion-like structuring in ternary surfactant-free microemulsions (SFME) and consequently, hydrogen-bonding-free microemulsions (HBFME) exist. The evaluated ternary systems were investigated by means of dynamic light scattering (DLS) and computer-based calculation methods. Theoretical COSMO-RS based calculations were applied to provide an explanation for different hydrotropic efficiencies, and COSMOplex calculations were used to predict and evaluate the propensity of the molecules to form mesoscale structures in SFME and HBFME. Microemulsion-like fluctuations could be observed in the COSMOplex simulations and correlate fairly well with the appearance of mesoscopic structures observed in SFME and HBFME, although the free energy differences in the formation of aggregate structures in the investigated systems are very small, in the range of 0.05 kcal mol −1 .